Vulnerability framework of tourism to natural disasters - Ak. Mohd Rafiq Ak. Matusin,; Chamhuri Siwar,; Sharina Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Natural disaster is a major challenge to tourism destinations. Thus, a vulnerability analysis is required as a part of disaster risk reduction to ensure their sustainability. This study aimed to present an analysis of the tourism vulnerability framework for those areas that face natural prone disasters. To achieve the study purpose, the framework was developed through a review of research papers that focusing on the application of vulnerability approach in sustainable tourism discourse. The search databases used for literature review including Google Scholar, SCOPUS and Science Direct. The primary result is discussed using the constructs of Vulnerability Framework for Sustainable Tourism Development (VFSTD), which composed of several elements: shocks-stressors, exposure, sensitivity and system adaptiveness. The VFSTF is fundamentally adopted from Turner Vulnerability Analysis in Sustainability Science, which highlights the integration of vulnerability approach and sustainability science as a system. For tourism as a core, VFSTD would helpful in clarifying the fundamental of vulnerability analysis and enhancing the effectiveness of risk reduction action for tourism in disaster-prone areas. Particularly, users of VFSTD would able to explore the factors and processes that create and perpetuate vulnerability to natural disasters in tourism destinations and elicit adjustment and feedback to encourage tourism sustainability more holistically.